Blastocyst stage transfer vs cleavage stage embryo transfer - Ann M Mangalraj; K Muthukumar; T K Aleyamma; Mohan S Kamath; Korula George (Wolters Kluwer Medknow Publications, 2009)
Objective: To evaluate the efficacy of blastocyst transfer in comparison with cleavage stage embryo in a similar cohort of women. Design: Retrospective analysis. Setting: University teaching hospital. Materials and Methods: Women aged 35 or less undergoing in vitro fertilization/intracytoplasmic sperm injection between January 2005 and December 2006 were included in the study. When four or more grade 1 embryos were observed on day 3, extended culture till day 5 was undertaken. This policy was compared with a cohort of women who had at least three grade 1 embryos on day 3 and who had undergone a cleavage stage embryo transfer during the time period of January 2002-December 2004. Primary outcome evaluated was implantation rate and clinical pregnancy rate. Results: Group 1 consisted of 50 women who underwent extended culture and blastocyst transfer. Group 2 comprised of 85 women who had cleavage transfer. The implantation rate for embryos transferred in group 1 was significantly higher than that for embryos transferred on day 3 (40.16% vs 11.43%). The clinical pregnancy rate was also significantly better with blastocyst transfer as compared with cleavage stage transfer (62% vs 29.76%). Significantly fewer embryos were required for transfer at the blastocyst stage compared with day 3 transfer (2.54 vs 3.45). Conclusion: In selected cases, blastocyst transfer with fewer embryos can be performed with high implantation and clinical pregnancy rates. This policy could lead to a reduction in the incidence of higher-order pregnancies.